A Novel Pricing Algorithm Based on Reward-Punishment Mechanism for Supply and Demand Balancing - Chen, Xiaofei; Weng, Liguo; Zhu, Haiyan; Lian, Deqiang (Frontiers in Energy Research, 2021)
Demand response (DR) is a powerful tool to maintain the stability of the power system and maximize the profit of the electricity market, where the customers engage in the pricing scheme and adjust their electricity demand proactively based on the price. In DR programs, most existing works are based on the assumption that the prediction of the electricity demand from customers is always accurate and trustworthy, which will lead to high cost and fluctuation of the electricity market once the prediction is obeyed. In this paper, we relax the condition and propose a heuristic reward and punishment mechanism to normalize the behavior of the customers such that actual demand is within a tolerable range. Then, a novel pricing scheme is designed to achieve the balance of supply and demand, which guarantees the maximum profit of the supplier. Finally, simulation results are constructed to demonstrate the effectiveness of the proposed mechanism.